The Relationship Between Smoking And The Formation Of Lung Cavity Lesions In Tuberculosis Patients At H Adam Malik General Hospital - Joseph Partogi Sibarani (International Journal of Health and Pharmaceutical (IJHP), 2024)
The purpose of this study is to ascertain whether smoking has any connection to the development of lung cavity lesions in tuberculosis patients at H Adam Malik General Hospital. This study is an observational, analytical, case-control investigation. In this investigation, 80 samples total 40 individuals who smoked and 40 non-smokers were used. How to choose a sample using the purposive sampling method. Information was gleaned from the medical files of H Adam Malik General Hospital's tuberculosis patients in 2021. The Chi Square test was used to examine the research data. According to the study's findings, 62.5% of the research sample's participants were men and 37.5% were women. The majority 28.7% are in the 46 to 55-year-old age range. According to the Brinkman Index, up to 28.8% of the sample's participants were heavy smokers. Lung cavity lesions are present in 46.25 percent of patients, as may be shown. Up to 30% of patients who smoke have lung cavity lesions. According to the analysis's findings, smoking was associated with the development of lung cavity lesions in tuberculosis patients at Adam Malik General Hospital with a value of p = 0.014 (p 0.05), and those patients who smoked had a risk of developing lung cavity lesions that was 3.115 times higher (OR = 3.115). This study's findings suggest that smokers with tuberculosis are three times more likely to develop lung cavity lesions.